Implementasi Bunker Safety Checklist Untuk Meningkatkan Keselamatan dan Pencegahan Pecemaran Selama Bunkering - Susanto; Khaeroman, Khaeroman; Widar Bayu Wantoro; Putranto, Wahyu Ari Putranto (Dinamika Bahari, 2024)
Bunkering on ships is a very important job with a high risk of danger. Bunkering is moving liquid fuel oil from a bunker barge or bunker terminal. The process of transferring oil has the potential to cause pollution. Pollution can occur if an operational error occurs, such as an overflow, pipe, or bunker hose breaking. Overflow is one factor that most contribute to oil spills during the bunkering process. Oil overflow incidents by ships can result in expensive claims, with cleanup costs, penalties, and environmental damage running into millions of dollars. Studies to reduce the risk of oil pollution from bunkering operations need to continue. This study was carried out to know the implementation of the bunker safety checklist. The study was conducted using a case study method strengthened by a literature study. The study was conducted on board MT. Fatmawati with Dead Weight Tonnase (DWT) 7762 metric tons. The ship is driven by a diesel engine with a power of 2721 kW at 195 RPM. The 100% HFO capacity stored on board is 531.44 m3. The ship can also carry an HSD of 119.77 m3 at 100% capacity—security and safety considerations. The maximum fuel capacity that can be loaded is in the range of 80 - 90%. The study results obtained by implementing the bunker safety checklist in bunkering activities are highly recommended. Bunkering will be well planned, from planning, estimating the fuel loaded, and executing to reporting. Safety requirements and pollution prevention due to oil spills can be avoided with work planned and recorded in a checklist.